The development of novel ionic liquid-based solid catalysts and the conversion of 5-hydroxymethylfurfural from lignocellulosic biomass - Liu, Xiaofang; Luo, Hangyu; Yu, Dayong; Pei, Zhengfei; Zhang, Zhuangzhuang; Li, Can (Frontiers in Chemistry, 2022)
Ionic liquids have attracted attention due to their excellent properties and potential for use as co-solvents, solvents, co-catalysts, catalysts, and as other chemical reagents. This mini-review focuses on the properties and structures of ionic liquids, the pretreatment of lignocellulosic biomass, and the development of novel ionic liquid-based solid catalysts for cellulose and hemicellulose derived HMF production.